Pembentukan Karakter Religius Melalui Pembiasaan Tahfidzul Qur'an Pada Siswa Kelas IV dan V (Studi Kasus di MIS Nurul Hikmah Sekura) - Tita Nia; Purniadi Putra; Rona (Jurnal Ilmiah Edukatif, 2023)
The purpose of this study is to reveal about: 1) The concept of forming religious character through the habituation of tahfidzul qur'an in grades IV and V at MIS Nurul Hikmah Sekura; 2) The process of forming religious character through the habituation of tahfidzul qur'an in grades IV and V at MIS Nurul Hikmah Sekura; and 3) The character that is formed through the habit of tahfidzul qur'an in class IV and V students at MIS Nurul Hikmah Sekura. This research uses a qualitative approach and a type of case study research. Data collection techniques using observation, interviews and documentation. The analysis technique used is data reduction, data display and data verification/conclusion. The results of the study show that: 1) The concept of forming religious character through habituation of tahfidzul qur'an in grades IV and V has fulfilled three concepts, namely: moral knowing, moral loving/feeling, and moral doing/acting. 2) The process of forming religious character through the habituation of tahfidzul qur'an in grades IV and V at MIS Nurul Hikmah Sekura goes through four stages, namely: the habituation stage, the stage of understanding or reasoning, the stage of application and the stage of reflection. 3) The characters formed by the habituation of tahfidzul qur'an in grades IV and V are: religious (values of worship), discipline, responsibility (values of trustworthiness), tabligh, respect for others, hard work (ruhul jihad), diligent (istiqomah) and likes to read.